Practice of kafa'ah in marriage and its urgency in society viewed from islam perspektive (Case Study in the Pitu Hamlet Community, Pitu Village, Pitu District, Ngawi Regency) - Puguh Fitri Setyo Widodo; Abid Nurhuda (Institute Of computer Science (IOCS), 2023)
Marriage is a reliable means of maintaining harmony, love, and affection. And to make this happen, it is necessary to pay attention to various things, one of which is related to equality or kafa'ah in marriage where most people do not know the term kafa'ah. As in the people of Pitu Hamlet, Pitu Village, Pitu District, Ngawi Regency, where young people aged 30-40 years are not married because there is no kafa'ah with a prospective wife, there are even many cases of divorce there due to the lack of kafa'ah between spouses. So the purpose of this study is to describe the practice of Kafa'ah in marriage and its urgency in society viewed from islam perspective. The method used is field research by collecting both primary and secondary data. Then analyzed with the model inductive namely reducing data, presenting data, and drawing conclusions. The results of this study indicate that kafa'ah is interpreted as a balance between husband and wife candidates starting from religion, heredity, work, and wealth, to being free from disgrace.